THE CONSTRUCTION OF CRITICAL DISCOURSE REGARDING THE FREE NUTRITIOUS MEALS PROGRAM ON THE @MENUEMBEGEJELEK ACCOUNT ON THE X PLATFORM - Alifia Fricila Rahman; Dyva Claretta (Adisam Publisher, 2026)
The Free Nutritious Meals Program (MBG) is an Indonesian government public policy that has elicited diverse responses in the digital public sphere, particularly on the X platform. This study aims to analyze the discourse construction of criticism directed at the MBG Program on the @menuembegejelek account using Norman Fairclough’s Critical Discourse Analysis, which encompasses the dimensions of text, discursive practices, and social practices. The study employs a descriptive-interpretive qualitative approach by examining seven posts published between February and June 2026, which were purposively selected based on their relevance to the research focus. Data were collected through digital observation, documentation, and literature review. The results show that, in the textual dimension, criticism is constructed through evaluative diction, metaphors, satire, irony, visual humor, rhetorical questions, modality, and intertextuality, which represent the MBG as a policy governance issue. In the discursive practices dimension, criticism is built through the recontextualization of news, government institution videos, memes, and user comments, thereby generating new meanings. In the social practice dimension, the critical discourse represents the ideologies of accountability, meritocracy, evidence-based policy, social welfare, and participatory democracy, which are used to question the legitimacy and implementation of the MBG Program.